Importance of preservation of the transversalis fascia in the repair of the posterior wall of the inguinal tract - Croci, Fabio; Pérez Penco, Ernesto; Rabellino, Joaquín; Cordal, Adriana (Cirugía del Uruguay, 1986)
The posterior wall of the inguinal tract is formed by a triple sheet the structure and physiology of which ensures contlnence in totum: perltoneum, fascia transversalis and the transversa fascia. The hernia failure represents the sectorial or diffuse insufficiency of the true transversalis fascia. Evident technical and evolutiva beneflts are derivad from the preservation of same. A description is provided of the method for identification and dissection of this issue in the course of inguinal hernia repair.